2016
DOI: 10.4236/health.2016.814157
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Thirst for Knowledge Regarding Hypertension among Rural Dwellers in Isunjaba, Imo State, Nigeria: A Qualitative Study

Abstract: Hypertension accounts for 13% of global mortality, is one of the most frequent causes of end stage kidney failure in the world, and has a 25% prevalence in Nigeria. Primary prevention based on comprehensive population-based intervention has been found most economical. Lifestyle modification is an essential part of management. It is important for the researcher to have a deep understanding of people's perceptions and attitudes to diseases like hypertension where effective interventions must address lifestyle ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…In this study, proven biomedical risk factors such as smoking, excessive alcohol intake, inadequate exercise, excessive fat and salt intake and stress and drug abuse were believed by both PHC workers and PHC clients to be major causes of hypertension. This is consistent with other studies on Nigerians [13, 14, 22] and in other parts of the world [2329]. However, the study by Beune et al [23] showed that beliefs about causes of hypertension differed between health workers and lay people with hypertension.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, proven biomedical risk factors such as smoking, excessive alcohol intake, inadequate exercise, excessive fat and salt intake and stress and drug abuse were believed by both PHC workers and PHC clients to be major causes of hypertension. This is consistent with other studies on Nigerians [13, 14, 22] and in other parts of the world [2329]. However, the study by Beune et al [23] showed that beliefs about causes of hypertension differed between health workers and lay people with hypertension.…”
Section: Discussionsupporting
confidence: 90%
“…Lay beliefs on the understanding of hypertension in terms of social related stressors are not new. Similar findings have been shown in studies on beliefs of hypertension in Nigeria [13, 14, 22] and in other places [2329]. However, description of meaning hypertension among Nigerians in terms of cultural understanding is relatively new and was only recently described in a similar study conducted by the authors on Nigerian immigrants to the United Kingdom [17].…”
Section: Discussionsupporting
confidence: 82%
“… 10 12–14 In particular, studies in the USA and UK have stressed that traditional and cultural beliefs and practices have an influence on perceptions regarding HTN among people of African descent. In SSA, a study, conducted in Zambia among adult rural participants reported a preference for using alternative medicines and herbs for BP treatment, 15 while another study in Nigeria found that while social support could contribute to compliance to HTN treatment, 16 even among people of the same ethnicity, there could be varied beliefs about HTN. These studies suggest that communities’ perceptions regarding illness influence how individuals understand and perceive their illness and could subsequently influence health outcomes for HTN and for other chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, almost half of the respondents expressed fatalistic views stating that self-monitoring BP cannot prevent hypertension if an individual is destined to have. These sociocultural perception and beliefs have been documented in previous studies, 22,25,26 and this justifies the continued need for tailored behavior change interventions to correct wrong misconceptions and promote appropriate health-care-seeking behaviors.…”
Section: Discussionmentioning
confidence: 67%